Coherent social policy of the EU member states - Swatek, Małgorzata (Publishing House of the Wrocław University of Economics, 2009)
This article attempts to demonstrate the significance of the coherent social policy of the European Union in combating negative social and economic phenomena such as poverty and income inequality. Particular attention is drawn at actions connected with activation of people on the labour market; it also discusses the role of non-govern-mental organisations and institutions in the social cohesion policy. There is no single common social model in Europe, which arises from different detailed regulations in the social policy of each country. However, we must admit that social systems in European countries share many qualities which determine their uniqueness in the international context and distinguish our continent from other regions of the world, in particular from the USA and the Asian region. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 425-431